2020
DOI: 10.1111/nyas.14416
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐mediated inflammation and coagulation effects in rats exposed to an inhaled analog of sulfur mustard

Abstract: Exposure of rats to 2-chloroethyl ethyl sulfide (CEES), an analog of sulfur mustard, can cause acute lung injury (ALI), resulting in increased inflammation and coagulation and altered levels of plasma microRNAs (miRNAs). Rats were exposed to aerosolized CEES and euthanized 12 h later for collection of tissue and plasma. Profiling of miRNAs in plasma, using a TaqMan-based RT-PCR array, revealed 14 differentially expressed miRNAs. Target gene prediction and pathway analysis revealed miRNA-mediated regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Proinflammatory cytokines are produced predominantly by activated immune cells which trigger inflammatory reactions. Based on the earlier reports and our own findings [ 89 , 221 ], IL-6 is clearly an important pro-inflammatory cytokine in pulmonary and non-pulmonary diseases, which can be regulated epigenetically. IL-6 in turn, can epigenetically regulate other molecular factors.…”
Section: Epigenetic Regulation Of Inflammationmentioning
confidence: 86%
See 1 more Smart Citation
“…Proinflammatory cytokines are produced predominantly by activated immune cells which trigger inflammatory reactions. Based on the earlier reports and our own findings [ 89 , 221 ], IL-6 is clearly an important pro-inflammatory cytokine in pulmonary and non-pulmonary diseases, which can be regulated epigenetically. IL-6 in turn, can epigenetically regulate other molecular factors.…”
Section: Epigenetic Regulation Of Inflammationmentioning
confidence: 86%
“…Even the tumor associated neutrophils (TANs) aid lung cancer tumorigenesis through increased expression of chemokine receptors such as CXCR3/4, CCR5/7 along with secretion of pro-inflammatory factors such as IL-6, IL-8 and MCP-1 [ 86 ]. IL-6 is produced at inflammation sites [ [87] , [88] , [89] ] and it promotes lung cancer metastasis [ 90 ]. High circulating levels of IL-6 associate with poor prognosis of lung cancer patients [ 91 ] thus making case for IL-6 blockage as an effective anticancer therapy [ 92 ].…”
Section: Inflammation and Cancer Connectionmentioning
confidence: 99%
“…In recent years, studies on ARDS patients have found that miRNA expression is abnormal. CEES [ 23 ] exposure can also lead to differential expression of miRNAs in rat plasma [ 24 ]. It has been found that miR-346 expression is upregulated in rats, targeting multiple mRNAs [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of miRNAs in the toxicity induced by 2chloroethyl ethyl sulfide (CEES), an inhaled monofunctional analog of SM, was elucidated recently by Rana et al in a cellular model and male Sprague-Dawley rats. 123 The effects observed in this study were acute effects, studied 12 h after CEES exposure in rats and 24 h after CEES exposure in the cell culture. The authors observed significant downregulation of miR-140-5p, which is a marker of ALI, in multiple organs of CEES-exposed rats and in rat airway epithelial cells as compared with the respective controls.…”
Section: Role Of Mirnas In 2-chloroethyl Ethyl Sulfide-induced Toxicitymentioning
confidence: 93%
“…125 Rana et al further proposed on the basis of their study that miR-140-5p could prove to be a useful target to mitigate the toxic effects of SM exposure. 123 Benefits of deciphering the role of miRNAs in SM-induced toxicity miRNAs have emerged as integral components in the regulation of the genetic machinery; however, their precise role in myriad of pathways is still relatively novel and unexplored in the field of biological sciences. Nonetheless, numerous studies on the role of miRNAs in SM-induced toxicity have been conducted that provide two benefits.…”
Section: Role Of Mirnas In 2-chloroethyl Ethyl Sulfide-induced Toxicitymentioning
confidence: 99%